2020
DOI: 10.5194/se-11-527-2020
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the depth and evolution of intrusions at resurgent calderas: Los Humeros (Mexico)

Abstract: Abstract. Resurgent calderas are excellent targets for geothermal exploration, as they are associated with the shallow emplacement of magma, resulting in widespread and long-lasting hydrothermal activity. Resurgence is classically attributed to the uplift of a block or dome resulting from the inflation of the collapse-forming magma chamber due to the intrusion of new magma. The Los Humeros volcanic complex (LHVC; Mexico) consists of two nested calderas: the outer and older Los Humeros formed at 164 ka … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 64 publications
8
33
0
1
Order By: Relevance
“…A local heat source could be assumed as located at greater depths transporting heat along permeable faults especially in the region close to Los Humeros Fault zone. Such a hypothesis would be in correlation with the analog and structural work by Urbani et al (2020) that suggests recent shallow magma emplacement in the region close to the Loma Blanca fault. Given the limited imaging capabilities of the data set used, this hypothesis would need to be confirmed with other geophysical and seismic imaging techniques such as ambient noise tomography.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…A local heat source could be assumed as located at greater depths transporting heat along permeable faults especially in the region close to Los Humeros Fault zone. Such a hypothesis would be in correlation with the analog and structural work by Urbani et al (2020) that suggests recent shallow magma emplacement in the region close to the Loma Blanca fault. Given the limited imaging capabilities of the data set used, this hypothesis would need to be confirmed with other geophysical and seismic imaging techniques such as ambient noise tomography.…”
Section: Resultssupporting
confidence: 65%
“…The main geological boundaries found from well and new petrophysical data were also found in our Vp model. The presence of two instrusive bodies supports the idea of resurgence at Los Potreros caldera (Norini et al, 2019;Urbani et al, 2020). Urbani et al (2020) suggest that intrusions in the region are the result of the inflation of the magma chamber at depth and may represent locations of local heat source(s).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Thus, in the field it is not possible to investigate the spatial extension of the intrusive bodies within the (meta-) sedimentary basement. However, Urbani et al (2020) concluded that the recent uplift within the Los Proteros caldera was caused by multiple intrusive bodies at a very shallow depth (425 ± 170 m to < 1000 m). Likewise, in Acoculco several intrusive bodies were identified at 1000 m depth already (below ground level, Avellán et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse faults of this type have been identified in natural cases of shallow-seated intrusions (e.g. Sibbett, 1988;Jackson and Pollard, 1990;Schofield et al, 2010;Wilson et al, 2016).…”
Section: Arroyo Grande and Maxtaloya Faultsmentioning
confidence: 99%